Effectiveness of the Asset Price Channel as a Monetary Policy Transmission Mechanism in Malawi: Evidence from Time Series Data - Tchereni, Betchani H. M.; Makawa, Ahmad; Banda, Fredrick (International Journal of Economics and Financial Issues, 2022)
This paper first, investigates the responsiveness of stock prices to changes in interest rates in Malawi, a low-income country in sub-Saharan Africa. Secondly, determines whether Gross Domestic Product of such economies respond significantly to changes in stock prices. Time series data from January 2001 to December 2019 are utilised. Unit root tests indicate that each variable is integrated of order one and the Johansen test for cointegration reveal that the variables are cointegrated, with one cointegrating equation. Therefore, a vector error correction model has been adopted to investigate the short and long-run dynamic relationship among the variables. Results of Granger causality tests and impulse response analysis indicate that stock prices do respond to changes in interest rates. Moreover, Gross Domestic Product also responds to changes in stock prices. Thus, contrary to previous studies, this paper finds that an asset price channel operating through stock prices exists in Malawi. More specifically, this study finds that variations in interest rates cause significant changes in stock prices which in turn cause changes in Gross Domestic Product. Among others, the study recommends that the monetary authorities should raise public awareness on investment opportunities available in stock markets.